Effect of Various Excipients on Theophylline-loaded Alginate Beads Prepared by Ionic Cross Linking Technique - Jahan, Sheikh Tasnim; Sadat, Sams Mohammad Anwar; Islam, Md Saiful; Jalil, Reza-ul; Chowdhury, Jakir Ahmed (Dhaka University Journal of Pharmaceutical Sciences, 2011)
Theophylline loaded sodium alginate beads were prepared by ionic cross linking technique using calcium chloride (CaCl2) as cross linking agents. The purpose of this work was to prepare sodium alginate beads as a device for the extended release of theophylline. Different excipients like sodium carboxy methyl cellulose, polyethylene glycol 4000, hydroxy propyl methyl cellulose, sodium starch glycolate, Eudragit L 100 and sodium lauryl sulphate were used to fabricate theophylline-alginate beads and their effect on drug release were investigated. In this study, the beads were characterized and evaluated in respect to their surface morphology, swelling index (SI) and in-vitro release characteristics. Beads were prepared by dropping a hot aqueous theophylline-alginate or theophylline-alginate-excipient solution into electrolyte solution. Alginate cross linked with electrolytes and beads were formed with entrapped drug. Beads were collected by decanting the solution and dried at room temperature. Surface of beads with various excipients revealed that smooth, dense and closely packed drug-polymer bonding was obtained when the excipients were changed. Beads in F 1 contain Eudragit L 100 that swelled highest at 3 hours with SI of 10.74 %. Sodium starch glycolate beads (F 4) swelled high up to 9.93 % at 2 hours. Dissolution studies were carried out in 900 ml of distilled water for 8 hours. Most of the formulations were fitted to Higuchi model. The drug release rate are shown in decreasing order: Eudragit L 100>Sodium carboxy methyl cellulose> Sodium lauryl sulphate> Sodium starch glycolate>Hydroxy propyl methylcellulose 5 cps>Polyethylene glycol 4000. The use of Eudragit L 100 was found to be promising because it released about 69 % of theophylline within 8 hours. It was found that among the hydrophilic polymers used, Sodium carboxy methyl cellulose showed 49 % theophylline release within 8 hours. The lowest amount of drug release was found with HPMC 5 cps and PEG 4000 which was about 26 % of drug release. Key words: Theophylline; ionic cross-linking technique; sodium alginate beads; swelling index; release kinetics. DOI: 10.3329/dujps.v9i1.7425 Dhaka Univ. J. Pharm. Sci. 9(1): 15-22 2010 (June)